RISK FACTORS FOR REPEATED ECTOPIC PREGNANCY - Nazarova, Саёра; Yakubova, Олтиной; Mamarasulova, Дилфузахон (International Journal of Scientific Pediatrics, 2025)
Relevance. Ectopic pregnancy is a serious threat to the reproductive health of women, and in some cases is the cause of death. The frequency of EP has a stable upward trend, amounting to 0.8-2.4% in relation to childbirth, a repeated episode occurs in 7.5-22% of women. The purpose of the study is to develop criteria for quantitative assessment of the degree of individual risk and a method for predicting the likelihood of repeated ectopic pregnancy. Materials and methods of the study. The results of a survey of 246 women living in the Andijan region were analyzed, of which 166 had two ectopic pregnancies and 80 had one episode of ectopic pregnancy. Correlation, regression and discriminant analysis according to Fisher were carried out on 48 features of the unified survey card using the SPSS 15 software package. Research results. To assess the degree of individual risk of recurrent ectopic pregnancy and to develop a method for individual prediction, the information significance and prognostic value of each risk factor were determined. Three degrees of risk were identified: high - with a sum of coefficients of 13 points or more (the probability of recurrent ectopic pregnancy is 90%); medium risk with a sum of 12 to 3 (the probability of recurrent ectopic pregnancy is 50%); and low from 2 points or less (the probability of pathology is less than 20%). Conclusion. A high information index of the occurrence of a recurrent episode of ectopic pregnancy has such signs as unfavorable social status, a history of infertility, previous surgeries, inflammatory diseases of the genitals, sexually transmitted diseases, the time from the appearance of the first clinical signs to the start of surgery, conservative operations on the fallopian tubes, complicated course of the postoperative period.